1994
DOI: 10.1007/bf00585940
|View full text |Cite
|
Sign up to set email alerts
|

Role of the macula densa in the control of renal renin gene expression in two-kidney/one-clip rats

Abstract: Abstract. This study was designed to examine whether macula densa function is involved in the changes of renal renin gene expression upon acute hypoperfusion of one kidney. To block macula densa function, rats with free access to salt and water were subcutaneously infused with furosemide (12 mg/day) for 6 days. Then, 4 days after the start of the infusion, the left renal arteries were clipped with 0.2-ram silver clips and renin mRNA levels in ipsilateral and contralateral kidneys, as well as plasma renin activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…On the other hand, it would also be conceivable that activation of renin gene expression by amlodipine would not be susceptible to contralateral suppression to the same dose as in 2kidney-lcip rats without additional treatment. The reason for such a resistance to renin gene suppression is not yet clear, but in previous experiments we have observed that inhibition of renin gene expression in the contralateral kidneys was less pronounced in 2kidney-lclip rats when the renin system was stimulated by additional treatment, for example, with furosemide (Schricker et al, 1994a) or converting enzyme inhibitors (Schricker et al, 1994b).…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, it would also be conceivable that activation of renin gene expression by amlodipine would not be susceptible to contralateral suppression to the same dose as in 2kidney-lcip rats without additional treatment. The reason for such a resistance to renin gene suppression is not yet clear, but in previous experiments we have observed that inhibition of renin gene expression in the contralateral kidneys was less pronounced in 2kidney-lclip rats when the renin system was stimulated by additional treatment, for example, with furosemide (Schricker et al, 1994a) or converting enzyme inhibitors (Schricker et al, 1994b).…”
Section: Discussionmentioning
confidence: 90%
“…Under physiological conditions, glomerular filtration rate and absolute proximal reabsorption are dependent on, and reflections of, effective circulating volume, and the macula densa is situated to serve as both a sensor and an effector of total salt and volume homeostasis; however, pathophysiological decreases in renal blood flow secondary to renal artery stenosis may also be sensed by the macula densa as a decrease in effective circulating volume. Although the underlying mechanisms for the elevated renin activity in these states were previously attributed solely to baroreceptor activation of renin, 1 recent studies by Kurtz and associates 7,8 have shown that macula densa-mediated renin release is also involved in mediating the increased renin expression in the 2-kidney, 1 clip model of RVH. In addition, these investigators have demonstrated an important role for prostanoids in mediating the increased renin expression in this model.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies have suggested that macula densa signaling may also contribute to increased renin production in RVH. 7,8 The conversion of arachidonic acid to prostaglandin H 2 by prostaglandin G 2 /H 2 synthase (cyclooxygenase) is a key enzymatic step in the regulation of prostaglandin synthesis. 9 Two isoforms of cyclooxygenase (COX) exist: constitutive (COX-1) and inducible (COX-2).…”
mentioning
confidence: 99%
“…[2][3][4][5] Moreover, several studies suggested that the cyclooxygenase products prostaglandin E2 and prostacyclin are involved in the renal baroreceptor mechanism. 6 -10 However, because blockade of prostaglandin formation did not attenuate the pressure dependent regulation of the renin system in other investigations, [11][12][13][14] the precise role of prostanoids in the renal baroreceptor mechanism is not entirely clear.…”
mentioning
confidence: 99%